PENGARUH KEPERCAYAAN MEREK TERHADAP LOYALITAS MEREK MELALUI KEPUTUSAN PEMBELIAN. (STUDI KASUS PELANGGAN KENDARAAN TRUK FUSO MEREK MITSUBISHI PADA PT. BOROBUDUR OTO MOBIL DI KOTA SEMARANG) - Dewi, Kiki Afrilia; Nugraha, Hari Susanta; Dewi, Reni Shinta (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
Customer loyalty to the brand is a very important concept, especially on condition that the level of competition is very tight with low growth. In such conditions on brand loyalty is needed so that the company can survive. There are four variables that will be used as independent variables in this study, namely, the predictability of the brand, the brand competence, confidence in the company, and brand preferences.This study was conducted to determine the effect of predictability brand, brand competence, confidence in the company, and brand preferences on purchasing decisions and customer loyalty Mitsubishi truck. In this study using sampling techniques respondent random sampling, the number of respondents as many as 92 respondents. Analysis of the data used is path analysis.The results showed that the predictability of the brand, the brand competence, confidence in the company, and brand preferences partially and simultaneously has significant influence on purchasing decisions and loyalty. Based on path analysis, purchasing decision is a mediating variable on customer loyalty. Suggestions for the company is better able to improve the quality of Mitsubishi products, advantages and its uniqueness, able to educate their customers and increase the safety equipment in the truck.